The effects of fire on the thermal environment of sagebrush communities. (April 2020) - Anthony, Christopher R.; Hagen, Christian A.; Dugger, Katie M.; Elmore, R. Dwayne
Abstract: Thermal heterogeneity provides options for organisms during extreme temperatures that can contribute to their fitness. Sagebrush ( Artemisia spp.) communities exhibit vegetation heterogeneity that creates thermal variation at fine spatial scales. However, fire can change vegetation and thereby variation within the thermal environment of sagebrush communities. To describe spatial and temporal thermal variation of sagebrush communities following wildfire, we measured black bulb temperature ( T bb ) at 144 random points dispersed within unburned and burned communities, for 24-h at each random point. We observed a wide thermal gradient in unburned (−7.3° to 63.3 °C) and burned (−4.6° to 64.8 °C) sagebrush communities. Moreover, unburned and burned sagebrush communities displayed high thermal heterogeneity relative to ambient temperature ( T air ). Notably, T bb varied by 47 °C in both unburned and burned communities when T air was 20 °C. However, fire greatly reduced the buffering capacity and thermal refuge of Wyoming big sagebrush ( A. tridentata wyomingensis ) communities during low and high T air . Furthermore, fire increased T bb in Wyoming big sagebrush and mountain big sagebrush ( A. t. vaseyana ) during the mid-day hours. These results demonstrate how fire changes the thermal environment of big sagebrush communities and the importance of shrub structure which can provide thermal refuge for organisms in burned communities during extreme low and high T air . Highlights: Unburned and burned sagebrush communities exhibit high thermal heterogeneity. Fire alters the thermal environment of Wyoming sagebrush communities. Fire reduces thermal refuge in Wyoming sagebrush communities. Shrub cover and height provide thermal refuge in burned sagebrush communities.